2018
DOI: 10.1002/jhet.3199
|View full text |Cite
|
Sign up to set email alerts
|

An Easy Synthetic Approach to Construct Some Ebselen Analogues and Benzo[b]selenophene Derivatives: Their Antioxidant and Cytotoxic Assessment

Abstract: in Wiley Online Library (wileyonlinelibrary.com). 2-(Chloroseleno)benzoyl chloride serves as a versatile building block for the synthesis of novel ebselen (2-phenyl-1,2-benzisoselenazol-3(2H)-one) analogues and benzo[b]selenophen-3(2H)-one derivatives. The antioxidant activity and cytotoxic evaluation of the newly synthesized compounds were implemented. Among all the synthesized compounds, 1-(3-hydroxybenzo[b]selenophen-2-yl)ethanone oxime (9) was the most potent antioxidant and the most cytotoxic compound as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Hence this method gives an easy synthetic entrance towards benzoselenophenopyrazoles. [60,61] Finally, due to their intrinsic electron deficiency caused by the fused pyrazole moiety the performance of iodolopyrazolium triflates in XB-based halide abstractions was investigated. In the solvolysis of benzhydryl halides with acetonitrile as the benchmark reaction iodolium salts of type 15 showed the highest activity outperforming previous reported bidentate XB-donors.…”
Section: Resultsmentioning
confidence: 99%
“…Hence this method gives an easy synthetic entrance towards benzoselenophenopyrazoles. [60,61] Finally, due to their intrinsic electron deficiency caused by the fused pyrazole moiety the performance of iodolopyrazolium triflates in XB-based halide abstractions was investigated. In the solvolysis of benzhydryl halides with acetonitrile as the benchmark reaction iodolium salts of type 15 showed the highest activity outperforming previous reported bidentate XB-donors.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 43 and 44 ( Figure 11 ) were reported the same year by Hamama et al; also in this case no selectivity was observed, the compounds being endowed with a low micromolar anti-proliferative activity measured in the MCF-7 cell line and in the normal human lung fibroblast cell line (WI-38) [ 124 ].…”
Section: Antiproliferative Activitiesmentioning
confidence: 95%
“…6,7 Interactions of ebselen with biological enzymes extended the inhibitory effects to antiviruses and antitoxins, laying an important foundation for the treatment of diseases and the production of drugs. 8−12 What is particularly exciting is its resistance to Corona Virus Disease 2019 (COVID- 19), which has spread worldwide in the first half of 2020. It has been found that for COVID-19, ebselen is a very promising lead compound to antiviral agent.…”
Section: Introductionmentioning
confidence: 99%